Quantitative Analysis of Aloins and Aloin-Emodin in Aloe Vera Raw Materials and Finished Products Using High-Performance Liquid Chromatography: Single-Laboratory Validation, First Action 2016.09. (22nd November 2019) - Kline, David; Ritruthai, Vicha; Babajanian, Silva; Gao, Quanyin; Ingle, Prashant; Chang, Peter; Swanson, Gary
Abstract: A single-laboratory validation study is described for a method of quantitative analysis of aloins (aloins Aand B) and aloe-emodin in aloe vera raw materials and finished products. This method used HPLC coupled with UVdetection at 380 nm for the aloins and 430 nm for aloe-emodin. The advantage of this test method is that the target analytes are concentrated from the sample matrix (either liquid or solid form) using stepwise liquid–liquid extraction (water–ethyl acetate–methanol), followed by solvent evaporation and reconstitution. This sample preparation process is suitable for different forms of products. The concentrating step for aloins and aloe-emodin has enhanced the method quantitation level to 20 parts per billion (ppb). Reversed-phase chromatography using a 250 × 4.6 mm column under gradient elution conditions was used. Mobile phase A is 0.1% acetic acid in water and mobile phase B is 0.1% acetic acid in acetonitrile. The HPLC run starts with a 20% mobile phase B that reaches 35% at 13 min. From 13 to 30 min, mobile phase B is increased from 35 to 100%. From 30 to 40 min, mobile phase B is changed from 100% back to the initial condition of 20% for re-equilibration. The flow rate is 1 mL/min, with a 100 μL injection volume. Baseline separation (Rs > 2.0) for aloins A and B and aloe-emodin was observed under this chromatographic condition. This test method was validated with raw materials of aloe vera 5× (liquid) and aloe vera 200× (powder) and finished products of aloe concentrate (liquid) and aloe (powder). The linearity of the method was studied from10 to 500 ppb for aloins A and B and aloe-emodin, with correlation coefficients of 0.999964, 0.999957, and0.999980, respectively. The test method was proven to be specific, precise, accurate, rugged, and suitable forthe intended quantitative analysis of aloins and aloe-emodin in raw materials and finished products. The S/N for aloins A and B and aloe-emodin at 10 ppb level were 12, 10, and 8, respectively, indicating our conservative LOD level at 10 ppb (the typical LOD level S/N is about 3). The S/N for aloins A and B and aloe-emodin at the 20ppb level were 17, 14, and 16, respectively, indicating our conservative LOQ level at 20 ppb (the typicalLOQ level S/N is about 10). The stock standard solution of a mixture of aloins and aloe-emodin and a working standard solution were found to be stable for at least 19 days when stored refrigerated at 2–8°C, witha recovery of 100 ± 5%.